Analysis Of Supply Chain Management In The Tofu And Tempeh Industry In Konda Village, Konda Sub District - resa pahlepi; Sarinah Sarinah; Sakir Sakir (Jurusan Ilmu dan Teknologi Pangan, Fakultas Pertanian,, 2022)
This study aims to analyze the supply chain in the tofu and tempeh industry in Konda Village. The method in this study is qualitative with primary data from field observations and questionnaire interviews. Data analysis used data reduction analysis, data presentation and drawing conclusions. The results showed that the supply chain management of tofu in the tofu and tempeh industry in Konda Village involved soybean suppliers, producers, diluents and final consumers. The supply chain of the tofu and tempeh industry in Konda Village has two channels. Channel I consists of suppliers - producers of the tofu and tempeh industry in Konda Village, channel II consists of producers - retailers - final consumers. The product flow flowing from upstream to downstream has 2 systems, delivered and delivered. Financial flows flowing from downstream to upstream have 2 systems, transactions and via banks. The flow of information flows from two directions including supply and demand.